Impulse oscillometry reference values and correlation with predictors in Turkish preschool children - (:unkn) unknown (TURKISH J PEDIATRICS, 2019)
Impulse oscillometry (IOS) is a noninvasive, rapid technique requiring passive cooperation that allows for evaluation of lung function through the measurement of airway resistance and reactance. There are no available reference values for Turkish children. This study is aimed to determine the reference values of IOS parameters and to study their correlation with height, weight, body mass index, and age as predictors in healthy Turkish preschool children. Healthy children between 3-7 years of age who were selected according to ERS/ATS criteria and followed at Kocaeli University outpatient clinic performed IOS. The correlation between the anthropometric predictor variables and resistance and reactance at 5-20 hertz (R5-R20 and X5-X20), the respiratory impedance at 5 hertz (Z5), resistance area (AX) and resonance frequency (Fres) were assessed by regression analysis and stepwise method. 151 children (93 female) with the mean age of 67.9 +/- 16.2 months participated in the study. Multilinear regression analysis for IOS values of all children revealed that resistance was significantly correlated with height and reactance was significantly correlated with age (p<0.05). For girls, height had a negative effect on R5-20, Z5, AX values, while age had a positive effect on X5-20 and a negative effect on Fres (p<0.05). For boys, weight had a negative effect on R520, Z5 values, while age had a positive effect on X15-20 and a negative effect on AX, Fres (p<0,05). This study provided reference values of IOS in healthy Turkish children that would be a useful guide for diagnosing and following respiratory diseases in preschool children.
Keywords: impulse oscillometry (IOS); reference values; preschool children; IMPEDANCE